A Case for the Need to Improve the Unilateral Double Taxation Relief for Estate Duty in South Africa - Maretha Retief (Potchefstroom Electronic Law Journal, 2024)
This article aims to address a specific problem statement, namely how the unilateral relief under the Estate Duty Act can be enhanced to alleviate the potential hardship of double estate taxation on cross-border estates. Double taxation is a common occurrence when a person owns properties in more than one country, which become part of their estate at the time of death and liable for estate tax. The limited estate tax treaty network causes countries to reconsider their unilateral relief provisions under their domestic legislation. South Africa faces the same challenge under the Estate Duty Act. This article highlights the areas where clarity is needed in relation to the type of foreign death duty that may qualify for tax relief, such as the scope of qualifying foreign property, the exchange rate applicable and the date on which the conversion should be done, as well as the limitations and conditions of the unilateral relief available under the Estate Duty Act. Insights are provided that could be considered for possible amendments to the Estate Duty Act to provide greater clarity and certainty in calculating the estate duty liability payable in South Africa.